IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN MATEMATIKA DI MAN 1 KOTA PROBOLINGGO - UMAR HAMDAN; NURYAMI NURYAMI; RIQQI QULUBI; M. YAHYA; BADRUT TAMAM; ISMATUL MAULA; FITRI WAHYUNI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
This study is a comprehensive review of the implementation of the Independent Curriculum in mathematics learning at MAN 1 Probolinggo City, focusing on the planning and implementation processes while identifying supporting and inhibiting factors. A qualitative descriptive method was used in this study, with key informants being mathematics teachers, Madrasah students, the Deputy Principal for Curriculum, and the Madrasah Principal. Data collection was conducted through in-depth interviews, classroom participant observation, and document review, including the Learning Modules and Learning Objective Flow. Findings indicate that teachers adapt to Learning Outcomes in planning and developing learning modules designed to incorporate differentiated learning. Meanwhile, learning activities are implemented differently, with differences in teaching methods, media use, formative evaluation, and efforts to integrate the Pancasila Student Profile Strengthening Practice (PSPPS). Key supporting aspects are: teacher commitment, madrasah support, key challenges related to uneven understanding, and lack of resources. This study presents a rich picture of how madrasahs adapt to the new curriculum and includes recommendations for improving future implementation.